PENGELOLAAN PENYALURAN DANA TUNJANGAN PROFESI GURU PEGAWAI NEGERI SIPIL - Poppy Rahmiaty Maelan; Meyzi Heriyanto; Lena Farida (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Management of Distribution of Professional Civil Servant Employee Benefit Fund. This study aims to find out the implementation of the distribution of the allowance fund of the PNSD teacher profession in the Education Office of Dumai City. Key informants are teachers ranging from Kindergarten, Elementary School, Junior High School and High School as many as 5 people. Methods of data collection is done by interview method. After the data collected then analyzed with qualitative descriptive approach. The result of research is known that the improvement of teacher profession certification followed by the provision of new teacher profession allowance can improve teacher welfare as measured, among others by decreasing the proportion of teachers who have additional work. The TPG planning process has not been accurate, as can be seen from the absence of a proper number of teachers who passed the certification, so that TPG can not be accommodated in the current year’s budget and potentially become arrears in the next year.